Pystorms: A simulation sandbox for the development and evaluation of stormwater control algorithms. (April 2023) - Rimer, Sara P.; Mullapudi, Abhiram; Troutman, Sara C.; Ewing, Gregory; Bowes, Benjamin D.; Akin, Aaron A.; Sadler, Jeffrey; Kertesz, Ruben; McDonnell, Bryant; Montestruque, Luis; Hathaway, Jon; Goodall, Jonathan L.; et al.
Abstract: Advances in cyber–physical technologies have enabled real-time sensing and adaptive control of stormwater infrastructure. These smart stormwater systems allow for inexpensive, minimally-invasive stormwater control interventions in lieu of new construction. However promising the area of smart stormwater control, there still remain barriers – for experts and novices alike – to access shared tools and methods for investigating, developing, and contributing to it. In an effort to make smart stormwater control research more methodical and accessible, we present pystorms, an open-source Python-based simulation sandbox that facilitates the quantitative evaluation and comparison of control strategies. pystorms consists of a collection of real world-inspired smart stormwater control scenarios on which any number of control strategies can be applied and tested via an accompanying Python programming interface and coupled stormwater simulator. pystorms provides a framework for the rigorous and efficient evaluation of smart stormwater control methodologies across diverse watersheds with only a few lines of code.